Shadowing property for the free group acting in the circle. Issue 1 (2nd January 2020) - Iglesias, Jorge; Portela, Aldo
ABSTRACT: For the free group F 2 acting in S 1, we will prove that if the minimal set for the action is not a Cantor set, then the action does not have the shadowing property. We will also construct an example, whose minimal set is a Cantor set, that it has the shadowing property.